2002
DOI: 10.1002/art.10586
|View full text |Cite
|
Sign up to set email alerts
|

Can serum biomarker assays measure the progression of cartilage degeneration in osteoarthritis?

Abstract: A loss of homeostasis in the maintenance of a healthy articular cartilage leads to the pathologic degeneration of articular cartilage in osteoarthritis (OA). The preservation of a functional articular cartilage enables the survival of a tissue that covers articulating surfaces in a diarthrodial joint. With synovial fluid, articular cartilage provides an almost frictionless articulation enabling painless joint movement. The extracellular matrix of articular cartilage provides this tissue with its great strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…This enigma regarding serum biomarker results has been reported in a human study 19 and has prompted debate regarding the apparent unpredictability of increased or decreased serum biomarker concentrations in response to degenerative changes in joints. 20 It should be noted that changes in serum are reflective of systemic turnover and do not specifically reflect changes that occur in a single joint. Because of hepatic metabolism, the half-lives of biomarkers are much shorter in blood than in synovial fluid, and the magnitude of the difference depends on the biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enigma regarding serum biomarker results has been reported in a human study 19 and has prompted debate regarding the apparent unpredictability of increased or decreased serum biomarker concentrations in response to degenerative changes in joints. 20 It should be noted that changes in serum are reflective of systemic turnover and do not specifically reflect changes that occur in a single joint. Because of hepatic metabolism, the half-lives of biomarkers are much shorter in blood than in synovial fluid, and the magnitude of the difference depends on the biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…25 Ideally, osteoarthritis biomarkers should be investigated in multiple body fluids (serum, urine, and synovial fluid). 20,21,27 Collection of urine and blood from patients is associated with less complications, compared with synovial fluid. However, synovial fluid should provide the most direct information about changes in the joint.…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage metabolism can be monitored by measurement of the synthesis and the degradation products of cartilagespecific collagens and proteoglycans, which are released into synovial fluid, serum, and urine as byproducts (14). Studies of cartilage turnover using these biomarkers have indicated significant changes that relate to the erosion of articular cartilage in arthritis (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…These include magnetic resonance imaging (MRI) (2) and molecular markers of joint tissue turnover (3)(4)(5)(6). Several recent studies have shown that MRI provides accurate and precise evaluation of the key joint structures, including articular cartilage, osteophytes, bone marrow, synovium, ligaments, and menisci, although most of these studies focused on cartilage assessment (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…A variety of molecular markers for joint tissue turnover have been described, and these markers differ in terms of their tissue specificity and sensitivity in detecting alterations in OA (3)(4)(5)(6). Among these, urinary excretion of specific fragments of C-terminal crosslinking telopeptide of type II collagen (CTX-II) has been shown to be associated with progression of joint damage in OA (19)(20)(21).…”
mentioning
confidence: 99%